PAJAK EKSPOR DAN PENGARUHNYA TERHADAP CPO INDONESIA - Benny Rachman; Adang Agustin (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2010)
This study aims to analyze the development of national CPO (Crude Palm Oil) export, the influence of the implementation of the export tax for the welfare of producers, and the competiveness of CPO. This study uses primary data and secondary data. The result of the study shows that (1) in tne period 2000-2007, the volume and value of exports of CPO increased were 18.07 and 37.63 % per year, respectively, (2) CPO export tax directly and proportionally reduce the local price of CPO, which in tye end reduce the price of TBS (Tandan Buah Segar). The higher export tax and the more disadvantages CPO producers and overall level of welfare to decrease with the high PE rate of CPO, and (3) Indonesia has a comparative and competitive advantages in the production od CPO, as indicated by the value DRCR < 1 and PCR < 1 (DRC = 0.66 and the PCR = 0.60).